Thermal Decomposition and Kinetic Studies of Pyrolysis of Spirulina Platensis Residue - Siti Jamilatun; Budhijanto Budhijanto; Rochmadi Rochmadi; Arief Budiman (International Journal of Renewable Energy Development, 2017)
Analysis of thermal decomposition and pyrolisis reaction kinetics of Spirulina platensis residue (SPR) was performed using Thermogravimetric Analyzer. Thermal decomposition was conducted with the heating rate of 10, 20, 30, 40 and 50oC/min from 30 to 1000oC. Thermogravimetric (TG), Differential Thermal Gravimetric (DTG), and Differential Thermal Analysis (DTA) curves were then obtained. Each of the curves was divided into 3 stages. In Stage I, water vapor was released in endothermic condition. Pyrolysis occurred in exothermic condition in Stage II, which was divided into two zones according to the weight loss rate, namely zone 1 and zone 2. It was found that gasification occurred in Stage III in endothermic condition. The heat requirement and heat release on thermal decomposition of SPR are described by DTA curve, where 3 peaks were obtained for heating rate 10, 20 and 30°C/min and 2 peaks for 40 and 50°C/min, all peaks present in Zone 2. As for the DTG curve, 2 peaks were obtained in Zone 1 for similar heating rates variation. On the other hand, thermal decomposition of proteins and carbohydrates is indicated by the presence of peaks on the DTG curve, where lignin decomposition do not occur due to the low lipid content of SPR (0.01wt%). The experiment results and calculations using one-step global model successfully showed that the activation energy (Ea) for the heating rate of 10, 20, 30, 40 and 50oC/min for zone 1 were 35.455, 41.102, 45.702, 47.892 and 47.562 KJ/mol, respectively, and for zone 2 were 0.0001428, 0.0001240, 0.0000179, 0.0000100 and 0.0000096 KJ/mol, respectively.Keywords: Spirulina platensis residue (SPR), Pyrolysis, Thermal decomposition, Peak, Activation energy.Article History: Received June 15th 2017; Received in revised form August 12th 2017; Accepted August 20th 2017; Available onlineHow to Cite This Article: Jamilatun, S., Budhijanto, Rochmadi, and Budiman, A. (2017) Thermal Decomposition and Kinetic Studies of Pyrolysis of Spirulina platensis Residue, International Journal of Renewable Energy Development 6(3), 193-201.https://doi.org/10.14710/ijred.6.3.193-201